2007
DOI: 10.4049/jimmunol.178.4.2113
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CD8+ T Lymphocyte Effector Function and Macrophage Inflammatory Cytokine Production by Retinoic Acid Receptor γ

Abstract: Vitamin A and its derivatives regulate a broad array of immune functions. The effects of these retinoids are mediated through members of retinoic acid receptors (RARs) and retinoid X receptors. However, the role of individual retinoid receptors in the pleiotropic effects of retinoids remains unclear. To dissect the role of these receptors in the immune system, we analyzed immune cell development and function in mice conditionally lacking RARγ, the third member of the RAR family. We show that RARγ is dispensabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 43 publications
7
47
1
Order By: Relevance
“…The kinetics of RA signaling is consistent with the transition of macrophage phenotypes after IR-AKI. 16,51 Our model is also consistent with data indicating that ATRA represses inflammatory cytokine production by cultured macrophages, [52][53][54][55] and PTECs secrete factors that induce expression of alternatively activated markers in cultured macrophages. [15][16][17] Our data indicate that RA signaling provides another layer of temporally and spatially controlled signaling that regulates dynamic changes macrophage phenotypes after AKI.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The kinetics of RA signaling is consistent with the transition of macrophage phenotypes after IR-AKI. 16,51 Our model is also consistent with data indicating that ATRA represses inflammatory cytokine production by cultured macrophages, [52][53][54][55] and PTECs secrete factors that induce expression of alternatively activated markers in cultured macrophages. [15][16][17] Our data indicate that RA signaling provides another layer of temporally and spatially controlled signaling that regulates dynamic changes macrophage phenotypes after AKI.…”
Section: Discussionsupporting
confidence: 78%
“…On this basis, we propose that inhibition of PTEC RA signaling decreases M2 spectrum macrophage markers, but at the same time a compensatory increase in local RA synthesis acts through a different mechanism to repress inflammatory renal macrophages after IR-AKI. Because in vitro studies indicate that RA has direct suppressive effects on inflammatory macrophages, [52][53][54][55] it is likely this is a direct effect of RA on renal macrophages ( Figure 10B). …”
Section: Discussionmentioning
confidence: 99%
“…Downregultion of RA-induced ␣4␤7 and CCR9 expression was observed in both dnRAR␣-expressing and RAR␣-deficient CD8 ϩ T cells and illustrated the requirement of RAR␣-RXR for CCR9 upregulation (68). In line with our studies, previous research showed that RAR␥ deficiency did not lead to any loss of RA-induced ␣4␤7 or CCR9 expression on CD4 ϩ or CD8 ϩ T cells when activated in vitro (82).…”
Section: Ra Regulation Of Ccr9supporting
confidence: 78%
“…These data suggest that RAR␥ may be involved in CD8 ϩ T-cell development in the thymus (152). However, when RAR␥ is deleted from hematopoietic compartment, it is without effect on CD8 ontogeny (82). Therefore, in our point of view, RAR␥ does not regulate CD8 ϩ T-cell survival.…”
Section: /Cd8mentioning
confidence: 60%
“…Therefore, based on our results it may be concluded that antigen processing cells (APCs) of OBI patients are unable to fully present HBcAg 18-27 epitopes to cytotoxic T-cells, hence, immune cells cannot completely eradicate HBV from infected hepatocytes. Additionally, it has been documented that CD8 positive cells can play key roles as cytokine producers during immune responses against viral infection (17). …”
Section: Discussionmentioning
confidence: 99%